Emotion in the digital age : technologies, data and psychosocial life - Ellis, Darren; Tucker, Ian (Writer on self-help techniques) (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Emotion in a Digital Age examines how emotion is understood, researched and experienced in relation to practices of digitisation and datafication said to constitute a digital age. The overarching concern of the book is with how emotion operates in, through, and with digital technologies. The digital landscape is vast, and as such, the authors focus on four key areas of digital practice: artificial intelligence, social media, mental health, and surveillance. Interrogating each area shows how emotion is commodified, symbolised, shared and experienced, and as such operates in multiple dimensions. This includes tracing the emotional impact of early mass media (e.g. cinema) through to efforts to programme AI agents with skills in emotional communication (e.g. mental health chatbots). This timely study offers theoretical, empirical and practical insight regarding the ways that digitisation is changing knowledge and experience of emotion and affective life. Crucially, this involves both the multiple versions of digital technologies designed to engage with emotion (e.g. emotional-AI) through to the broader emotional impact of living in digitally saturated environments. The authors argue that this constitutes a psycho-social way of being in which digital technologies and emotion operate as key dimensions of the ways we simultaneously relate to ourselves as individual subjects, and to others as part of collectives. As such, Emotion in a Digital Age will prove important reading for students and researchers in emotion studies, psychology, science and technology studies, sociology, and related fields"--
OCLC-licensed vendor bibliographic record.
Keywords: Emotions; Information technology -- Psychological aspects; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General